Reprodução e recrutamento do camarão sete-barbas: Uma espécie ameaçada pela explotação no sudeste do Brasil - da Silva, Evelyn Raposo; Sancinetti, Gustavo Sérgio [UNESP]; Fransozo, Adilson [UNESP]; Azevedo, Alexandre; da Costa, Rogério Caetano [UNESP] (My University, 2015)
This study evaluated the reproductive period and recruitment of the threatened exploitation shrimp Xiphopenaeus kroyeri (Heller) in the southeast coast of Brazil. Monthly samples were carried out from March 2008 to February 2010 distributed in stations located inside (5, 10 and 15 m depth) and outside (25, 35 and 45 m depth) areas using a fishery boat equipped with an otter-trawl net. Water samples were taken for determination of temperature and salinity, and sediment samples for determination of texture and organic matter content. The reproductive period was determined by monthly amount (%) of females with mature gonads (ED+DE). The differences in sex ratio were tested using a Chi-square (χ2) test. A Principal Components Analysis (PCA) was performed for an overview of the environmental variables and Redundancy Analysis (RDA) was performed to assess the relationship between abiotic factors and reproductive activity and recruitment. The size (carapace length) at the onset of sexual maturity was 10 mm and 12 mm for males and females, respectively. Reproductive females (based on gonad development) were found in all sampled months, with remarket or conspicuous peaks during winter and summer. The input of young recruits occurred one to two months after the increase of reproductive females. It was verified an optimal of temperature range for reproductive females, from 21 to 24 °C. These results provide subsidies that can assist making decisions about protecting priorities and in monitoring the population stocks of this important fishery resource.
Reproduction and recruitment of the seabob shrimp: A threatened exploitation species in southeastern of Brazil
Keywords: Macaé; Reproductive biology; Xiphopenaeus kroyeri